Heart Disease and its Consequence in Pregnancy - Wahid, Fatima; Begum, Firoza; Kulsum, Umme; Fatema, Kaniz; Sharmin, Farzana; Kaman, SM Mustafa (University Heart Journal, 2012)
The aim of the study is to evaluate the types of heart disease common in our pregnant woman and to assess its influence on the maternal outcome. This was a prospective observational study. The study was carried out in the department of obstetrics & Gynecology in BSMMU from Jan 2006 to Dec 2006. Thirty-five consecutive cases with heart diseases were included in the study. Out of 35 Cases, 26(74.3%) were suffering from rheumatic heart diseases and only 9 (25.7%) patients were suffering from congenital heart disease. Based on New York heart Association (NYHA) functional classification, 28(80%) belonged to NYHA class I, 5 (71.212%) belonged to NYHA class II and 2(28.57%) belonged to class III heart disease on presentation. The number of caeserian section was 33(94.28%) and normal vaginal delivery (5.71%). In this study only 1 woman of NYHA III disease expired. DOI: http://dx.doi.org/10.3329/uhj.v7i1.10201 UHJ 2011; 7(1): 7-9